Volume/perfusion ratio from lung SPECT/CT - Schaefer, Wolfgang Michael; Knollmann, Daniela; Avondo, Jerome; Meyer, Andreas (Nuklearmedizin - NuclearMedicine, 2018)
Aim: In pulmonary emphysema lung volume reduction procedures (LVRP) can optimize respiratory pump function. Identification of the most affected lobe can be reached using relative lobar volume (relVol) from CT, but this approach disregards the corresponding lobar perfusion. The aim of the study was therefore to establish a new parameter combining relVol from CT and relative perfusion (relPerf) from perfusion SPECT as a single parameter (volume/perfusion ratio (VPR)) to optimize the identification procedure.Methods: As a proof of principle VPR was calculated from hybrid V-/P-SPECT/CT scans from 20 patients with severe pulmonary emphysema (SPE) before LVRP. Lung V-/P-SPECT/CT (Siemens SymbiaT) was done with Technegas and 99mTc-MAA. Quantification of lobar perfusion from scintigraphy and volume from CT was performed using “HERMES Hybrid 3D – Lung Lobe Quantification”. Using normal ranges – from 12 patients with suspected pulmonary embolism and normal lung structure and perfusion – all lobes were classified as normal or abnormal to identify targets for LVRP.Results: Normal values for VPR: right upper lobe 1.09 ± 0.10, middle lobe 1.31 ± 0.31, right lower lobe 0.87 ± 0.08; left upper lobe 1.09 ± 0.11, left lower lobe 0.87 ± 0.12. In the 20 SPE patients there were only 7 lobes with pathological values for rel- Vol, 14 lobes with pathological values for rel- Perf but 31 lobes with pathological VPR.Conclusion: Estimation of VPR from lung SPECT/CT enables a combined view of lobar volume and perfusion with one parameter. In SPE patients VPR allows identifying possible target structures with much higher sensitivity than when using relPerf or relVol alone. The specificity and the prognostic value of this new parameter have to be tested in a clinical trial.
Keywords: Pulmonary emphysema; lung volume reduction; lung perfusion scintigraphy